Comparison of fruit quality and GC–MS-based metabolite profiling of kiwifruit 'Jecy green': Natural and exogenous ethylene-induced ripening. (1st November 2017) - Lim, Sooyeon; Lee, Jeong Gu; Lee, Eun Jin
Highlights: 'Jecy green' kiwifruit was first bred in Korea in 2007. Kiwifruit were ripened without (naturally) or with exogenous ethylene (200 μL/L for 12 h). Concentrations of ascorbic acid and arabinose linearly decreased with kiwifruit ripening. Sucrose, myo -inositol, citric acid, and malic acid were higher in naturally ripe kiwifruit. Sensory parameter was not statistically different between two groups. Abstract: We applied exogenous ethylene to 'Jecy green' kiwifruit to elucidate the differences in fruit quality and metabolite profiling between naturally ripe (NR) and ethylene-induced ripe (ER) kiwifruit. Kiwifruit were exposed to ethylene (200 μL/L) for 12 h at 20 °C and maintained for 9 days at 20 °C. Two metabolites of ascorbic acid and arabinose significantly decreased during kiwifruit ripening regardless of the ripening method. The concentrations of sucrose, myo -inositol, citric acid, and malic acid in NR fruit were substantially higher than those in ER fruit, while the concentrations of fructose, glucose, and quinic acid in ER fruit were higher than those in NR fruit. NR and ER kiwifruit were statistically similar in regard to overall sensory profile, even though the metabolite profiling showed a little difference. The application of ethylene to 'Jecy green' kiwifruit to regulate ripening for commercial purposes can result in good quality fruit without side effects.